"Samba" Fish Catching Operations in the seagrass meadows of Selayar Island, Indonesia. (April 2019) - Marimba, A A; Ambo-Rappe, R; Nafie, Y A La; Unsworth, R K F
Abstract: Seagrass meadows around the world are under threat and most are in decline, including the extensive meadows along the western coast of Selayar Island, Indonesia. In the 1980s these seagrass meadows were still in good condition, as evidenced by the abundance and variety of gastropods which could be caught at high tide using a push net. This Activity has now stopped and shell collection can only be done during low tide. Around 60% of remaining seagrass meadows have been damaged through fishing with a pulled or pushed gear, including traditional " samba " seine net and " sogoro " push net, as well as trampling during gleaning activities. This study focused on the operation of "samba" in Selayar Island seagrass meadows from 2014 to 2017. Although this fishing gear was prohibited under a Government regulation in 2015, it is still operated on a limited basis by local fishermen. The samba is a small scale seine net operated by 3 fishermen. A boat pulls a leading rope to which coconut leaves are attached so that it also serves as a tool to scare fish. The fishermen pull the rope around to form a trap surrounded by a semi-circular barrier of polyethylene netting. One side of the barrier net is connected to the lead rope, and the trap is gradually closed in from a wide circle until all the fish are confined in a small trap. The samba catch is generally comprised of coral reef and seagrass associated fish families such as Acanthuridae, Balistidae, Chaetodontidae, Labridae, Lethrinidae, Lutjanidae, Scaridae, Siganidae and Zanclidae. With increased surveillance of destructive activities around Selayar Island there has been some improvement in seagrass condition, so that it can be hoped that these seagrass meadows will continue to support the fish, green turtles and dugongs living there.